Technological Innovation in Public Sector Reform : Chile's Public Procurement e-System - Orrego, Claudio; Osorio, Carlos; Mardones, Rodrigo (World Bank, Washington, DC, 2012)
Chile's government has used information technology to achieve a customer-driven public sector that is more transparent, efficient, and accountable. Chile wanted to put the government at the service of the people, and so pursued technological innovations that enable the government to meet citizens' needs simply, quickly, and efficiently. To that end, the government developed an information technology strategic plan for 1998-2000. One area in which the success was particularly distinguished was the comprehensive reform of the public procurement system. In just a short period, reform has generated clear savings, created a better information market, and increased transparency and accountability in government procurement.